Evaluation of HE4 as a prognostic biomarker in uterine cervical cancer,. (2023) - Dubey, Harshita; Ranjan, Amar; Durai, Julieana; Khan, M.A.; Lakshmy, R.; Khurana, Sachin; Gupta, Swati; Meena, Jyoti; Ray, M.D.; Tanwar, Pranay; Chopra, Anita; Tiwari, Sanat
Highlights: In uterine cervical cancer, the currently used most common biomarkers for the diagnosis or prognosis are squamous cell carcinoma antigen (SCC-Ag) and CA125. Raised serum level of SCC-Ag and CA125 are seen in 64% & 42.6% of squamous type of UCC respectively (1). Serum level of HE4 was positive in 78%, while negative in 22% of UCC. It has sensitivity and specificity 78.12% and 88.89% respectively. Serum level of HE4 has a far better result among available biomarkers in the diagnosis of UCC. HE4 seems to be close to an ideal screening biomarker for uterine cervical cancer as described by Clarke-Pearson DL 2009 (2). Serum level of HE4 may be considered a standard biomarker for cervical cancer. Abstract: Introduction: Uterine cervical cancer (UCC) is the fourth most common health problem worldwide among women. Currently available biomarkers CA125, CA199, and CEA for diagnosis or prognostic evaluation of UCC have not got widespread acceptance. Method: Whole blood samples of 64 patients with UCC were collected along with 63 healthy females and tested for serum levels of HE4 (sHE4). A cut-off value for positive result 64.0 pmol/L was set. Statistical analysis of different clinical variables was done. Result: Serum level of HE4 has a significant role in the diagnosis of uterine cervical cancer. Its level increases with age, higher parity ( P  < 0.05), stage ( P  < 0.16), tumor size, and parametrial invasion. Negative result was seen with vaginal invasion, lymph node involvement & cases which had recurrence. Various histological types showed variable results. So the serum level of HE4 (sHE) level may play a role in the diagnosis & therapeutic monitoring of UCC. But the prognostic evaluation needs further studies. Conclusion: sHE4 is useful in the diagnosis of cervical cancer, but its prognostic significance is under the question marks. It may be associated with higher values in higher stages. Higher parity of the patient is associated with higher level of HE4 in UCC.